2015
DOI: 10.1152/jn.00992.2014
|View full text |Cite
|
Sign up to set email alerts
|

Training voluntary motor suppression with real-time feedback of motor evoked potentials

Abstract: Majid DS, Lewis C, Aron AR. Training voluntary motor suppression with real-time feedback of motor evoked potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…UP training, in particular, resulted in an 83.8% increase of MEP amplitudes from baseline, while downregulation of MEP amplitude was possible eg. see 29 but more difficult (30.6% decrease from baseline). Once acquired, volitional control of corticomotor excitability was retained for at least 6 months and could be performed even without online feedback indicating true, long-term learning 33 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…UP training, in particular, resulted in an 83.8% increase of MEP amplitudes from baseline, while downregulation of MEP amplitude was possible eg. see 29 but more difficult (30.6% decrease from baseline). Once acquired, volitional control of corticomotor excitability was retained for at least 6 months and could be performed even without online feedback indicating true, long-term learning 33 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that it is possible to gain voluntary control over activity in the central nervous system if appropriate neurofeedback is embedded in a reinforcement learning task, with food rewards for animals 14,15 and visually rewarding stimuli for humans 19,29 . Here we confirm that this approach is also suitable for learning how corticomotor excitability can be bidirectionally up- or down- regulated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most published TMS studies investigate cortical physiology at rest, some groups have examined cortical excitability/inhibition during mental preparation for action 10 and during different cognitive states that may be reflected in motor cortex physiology. 11,12,13,14 This functional TMS (fTMS) approach requires online TMS measurements while participants are performing behavioral tasks, thus allowing one to probe cortical changes that are state-dependent with high temporal resolution. Providing real-time information on neurophysiologic changes in such a manner broadens the physiologic investigation of motor control 15,16 and neuropsychiatric conditions 17,18,19,20 .…”
Section: Introductionmentioning
confidence: 99%